Neurofibromatosis Type 1 and Diabetes Mellitus: An Unusual Association - Bayram Ozhan; Ali Aykan Ozguven; Betül Ersoy (Case Reports in Endocrinology)
Neurofibromatosis type 1 is a multisystemic disease. It may manifest as abnormalities of the nervous tissue, bones, soft tissue, or skin. Autoimmune disease associated with NF1 can be seen. Diabetes mellitus is rarely seen in association with NF1. Here, we report a case with established NF1 who also had a diagnosis of diabetes mellitus.